2011
DOI: 10.1007/s00425-011-1402-3
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum regulates oxalate secretion and plasma membrane H+-ATPase activity independently in tomato roots

Abstract: We demonstrated that aluminum (Al)-induced oxalate secretion and plasma membrane (PM) H(+)-ATPase activity in tomato (Lycopersicon esculentum 'Hezuo903') roots were poorly correlated. In addition, vanadate, an inhibitor of PM H(+)-ATPase, had no effect on Al-induced oxalate secretion, but significantly inhibited enzyme activity. An anion channel inhibitor phenylglyoxal inhibited oxalate secretion, but not PM H(+)-ATPase activity. Exposure of tomato roots to 10 μM LaCl(3) also stimulated PM H(+)-ATPase activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…They concluded that the Al-induced secretion of malate from wheat roots was accompanied by changes in PM surface potential and activation of H + -ATPase [118]. However, the Al-induced changes of root PM H + -ATPase activity were not associated with oxalate secretion in two tomato cultivars differing in the ability to secrete oxalate under Al stress [66]. Other studies showed Al inhibited root PM H + -ATPase activity in barley [119], squash ( Cucurbita pepo ) [120], and rice bean [121].…”
Section: Aluminium-induced Secretion Of Organic Acid Anions From Rmentioning
confidence: 99%
“…They concluded that the Al-induced secretion of malate from wheat roots was accompanied by changes in PM surface potential and activation of H + -ATPase [118]. However, the Al-induced changes of root PM H + -ATPase activity were not associated with oxalate secretion in two tomato cultivars differing in the ability to secrete oxalate under Al stress [66]. Other studies showed Al inhibited root PM H + -ATPase activity in barley [119], squash ( Cucurbita pepo ) [120], and rice bean [121].…”
Section: Aluminium-induced Secretion Of Organic Acid Anions From Rmentioning
confidence: 99%
“…Unfortunately, few studies have focused on the response of tomato to Al stress. In a previous study, we characterized root organic acid anions secretion from tomato roots [23]; however, the underlying molecular basis is unknown. In the preset study, we aimed to provide a comprehensive view of the NAC gene family in tomato and to identify members involved in the response to Al stress.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, wheat ( Triticum aestivum ), Arabidopsis thaliana and oilseed rape ( Brassica napus ) release malate for Al detoxification (Delhaize et al 1993; Ligaba et al 2006; Hoekenga et al 2003), whereas snapbean ( Phaseolus vulgaris ), rice bean ( Vigna umbellata ), maize ( Zea mays ), and soybean ( Glycine max ) secrete citrate to detoxify Al (Miyasaka et al 1991; Pellet et al 1995; Yang et al 2000; Liu et al 2013; Yang et al 2006). Oxalate is exuded from roots of buckwheat, tomato and spinach ( Spinacia oleracea ) under Al stress (Ma et al 1997; Zheng et al 1998; Yang et al 2005; Yang et al 2011). Recently, genes responsible for the Al-activated secretion of malate and citrate have been identified in plants (Furukawa et al 2007; Magalhaes et al 2007; Sasaki et al 2004), but genes required for oxalate release are still unknown.…”
Section: Introductionmentioning
confidence: 99%